2020
DOI: 10.3390/ani10101798
|View full text |Cite
|
Sign up to set email alerts
|

Microbiome Shift, Diversity, and Overabundance of Opportunistic Pathogens in Bovine Digital Dermatitis Revealed by 16S rRNA Amplicon Sequencing

Abstract: This study analyzed the diversity and phylogenetic relationship of the microbiome of bovine digital dermatitis (BDD) lesions and normal skin from cattle foot by using 16S rRNA amplicon sequencing. Three BDD samples and a normal skin sample were pre-assessed for analysis. The Illumina Miseq platform was used for sequencing and sequences were assembled and were categorized to operational taxonomic units (OTUs) based on similarity, then the core microbiome was visualized. The phylogeny was inferred using MEGA7 (M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 33 publications
2
4
0
Order By: Relevance
“…Treponema spp. were present at low levels even in samples from healthy cows which is consistent with previous studies that have shown their abundance increasing in active BDD lesions [1,6,35].…”
Section: Discussionsupporting
confidence: 92%
“…Treponema spp. were present at low levels even in samples from healthy cows which is consistent with previous studies that have shown their abundance increasing in active BDD lesions [1,6,35].…”
Section: Discussionsupporting
confidence: 92%
“…Treponema spp. were present at low levels even in samples from healthy cows which is consistent with previous studies that have shown their abundance increasing in active BDD lesions [1,6,33]. Ruminococcaceae from the Firmicutes phylum were the most abundant family and are also dominant in the bovine faecal microbiome [34].…”
Section: Discussionsupporting
confidence: 89%
“…OTU 150 was classified similarly and was more abundant in RB51-vaccinated elk at Postcalve and Necropsy. While M. feliminutum is typically associated with felines, it has been observed previously in bovine skin lesions (124), and other members of the genus Mycoplasma are associated with bovine reproductive disease (89,125). Finally, OTU 316 was classified as Fusobacterium necrophorum by BLAST analysis and was significantly more abundant in vaccinated elk at Precalve.…”
Section: Time and Vaccination Status Affect The Relative Abundance Of...mentioning
confidence: 87%